Combination of caudal epidural steroids with oral gabapentin for radicular low back pain: a prospective observational study - Singh, Grisuna; Thapa, Binod; Gurung, Kiran; Gyawali, Nirmal (Journal of Society of Anesthesiologists of Nepal, 2019)
Introduction: The physical, socioeconomic and psychological burden of low back pain is enormous. The poor socioeconomic condition and geographical constrains confines people to limited health facilities. The objective of the study was to evaluate whether combination of caudal epidural steroids with local anaesthetics and gabapentin is effective for radicular low back pain in the rural Nepal setting. Methods: It was a prospective observational study including 300 patients with radicular low back pain done over a period of 6 months (13/4/2016 to 30/10/2016). All participants received caudal epidural steroid injection (6ml 2% Xylocaine with adrenaline plus Depomedroxy steroid 80mg plus 12 ml distilled water) and 200 mg gabapentin daily for three months. All patients were followed up for three months and were evaluated. Results: Mean age of presentation was 41.21 years (SD ± 11.02) with majority of farmers (42.31%). Mean Numerical Rating Scale at the baseline was 8.01(SD±1.00) and at the first follow up was 3.98 (SD±0.83) (p <0.001). Mean Oswestry Disability Index at baseline was7.85 (SD±0.98) and at the first follow up was 4.04 (SD±0.80) (p <0.001). Straight Leg Raising Test at baseline was less than 70° in 84.7% which improved to more than 70° in 87.9% of the patients (p-value <0.001). Conclusion: Caudal epidural steroids combined with gabapentin is safe, economical and technically less demanding. This treatment modality can be used with good outcomes in the rural areas with limited diagnostic and therapeutic facilities.